PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN SISWA KELAS IV SDN 058119 PEMATANG SENTANG - Ilhamuddin; Marah Doly Nasution (STKIP Subang, 2026)
This research is motivated by the phenomenon of low mathematics learning outcomes on fraction material in class IV of SDN 058119 Pematang Sentang, where only 26.67% of students were able to achieve the Minimum Completeness Criteria (KKM) of 65. The main problem stems from the use of conventional lecture methods which cause students to become passive and have difficulty understanding abstract fraction concepts. The purpose of this study is to improve mathematics learning outcomes through the application of the Numbered Heads Together (NHT) type cooperative learning model. The research method used is Classroom Action Research (PTK) with the spiral design of the Kemmis and McTaggart model carried out in two cycles for 15 class IV students. Data collection techniques included learning outcome tests and student activity observations. The results showed a consistent improvement, where classical learning completeness in the pre-cycle was 26.67% (4 students) with an average of 54.67, increased to 60.00% (9 students) with an average of 68.40 in cycle I, and reached a maximum completeness of 100.00% (15 students) with an average of 79.67 in cycle II. Student participation activity also increased significantly from